Effects of hypertension and ovariectomy on rat hepatocytes. Are amlodipine and lacidipine protective? (A stereological and histological study) - Hakan DURSUN; Fatih ALBAYRAK; Abdullah UYANIK; Nuri Osman KELEŞ; Polat BEYZAGÜL; Ednan BAYRAM; Zekai HALICI; Zuhal Berrin ALTUNKAYNAK; Halis SÜLEYMAN; Nihat OKÇU; Bünyamin ÜNAL (Turkish Journal of Gastroenterology, 2019)
-